Factors Inhibiting the Implementation of the Merdeka Curriculum in Social Studies Learning at SMP Negeri 1 Kubung - Nofrin, Silvi May; Putri, Desi Armi Eka; Ikhwan, Ikhwan (The Future of Education Journal, 2025)
This research is motivated by changes in the national curriculum that require educational institutions to become more autonomous, adaptive, and focused on the holistic development of student competencies. However, in practice, the implementation of the Independent Curriculum, particularly in Social Studies subjects, continues to face various obstacles. This study aims to description the inhibiting factors in the implementation of the Independent Curriculum in Social Studies learning at SMP Negeri 1 Kubung, Solok Regency. The study was conducted at SMP Negeri 1 Kubung, located on Jl. Tampuniak Selayo, Solok Regency. A qualitative approach was employed, using data collection techniques including interviews, observations, and documentation. The key informants in this study were Social Studies teachers for grades VII, VIII, and IX, as well as students. Additional informants included the principal, vice principal for curriculum affairs, parents, and the school supervisor. The data were analyzed through three stages: data reduction, data display, and conclusion drawing. The results revealed several main inhibiting factors, including limited teacher understanding of the curriculum’s concepts and implementation, insufficient training and mentoring, inadequate facilities and infrastructure, and low student engagement in the learning process. These findings highlight the need for strategies to strengthen teacher capacity and institutional support, ensuring that the implementation of the Independent Curriculum proceeds effectively and in line with its intended objectives.